Association of pyrin mutations and autoinflammation with complex phenotype hidradenitis suppurativa: a case–control study. (20th February 2019) - Vural, S.; Gündoğdu, M.; Gökpınar İli, E.; Durmaz, C.D.; Vural, A.; Steinmüller‐Magin, L.; Kleinhempel, A.; Holdt, L.M.; Ruzicka, T.; Giehl, K.A.; Ruhi, H.I.; Boyvat, A.
Summary: Background: Hidradenitis suppurativa (HS) is a rare, debilitating neutrophilic dermatosis characterized by chronic inflammation of hair follicles. Many inflammatory conditions may accompany HS. Objectives: To investigate the association of variants of the MEFV gene with a complex HS phenotype. Methods: Firstly, we identified the clinical characteristics of 119 patients with HS with a complex phenotype (Hurley stage III disease and/or additional inflammatory symptoms). Then, we searched for MEFV variants among these patients. The odds ratios (ORs) for pathogenic MEFV mutations were calculated using data from these patients with HS and 191 healthy controls. Results: The male/female ratio was higher, and the mean age of onset was earlier, in our complex HS group compared with patients with HS in general. Five of the patients with HS (4·2%) had a diagnosis of familial Mediterranean fever (FMF) with a standardized morbidity ratio of 45 [95% confidence interval (CI) 16·50–99·84, P < 0·001] when compared with the frequency of FMF in the general Turkish population. Of the patients with complex HS, 38% were positive for pathogenic variants of MEFV . The OR for carrying a pathogenic MEFV allele was 2·80 (95% CI 1·31–5·97, P < 0·001). Conclusions: The frequency of MEFV mutations in the group of patients with complex HS was higher than that in healthy controls, suggesting that MEFV mutations may contribute to the pathogenesis of HS. Understanding the role of autoinflammation in HS is of fundamental importance for the development of novel therapies. Abstract : What's already known about this subject? Hidradenitis suppurativa (HS) is a neutrophilic dermatosis with an unclear pathogenesis, but immune dysregulation has been implicated. MEFV mutations are reported in several patients with PASH syndrome (pyoderma gangrenosum, acne and HS), which is a syndromic form of HS. What does this study add? Pathogenic MEFV variants are more frequent in patients with complex HS than in healthy controls. HS in syndromic forms [PASH, PAPASH (pyrogenic arthritis, pyoderma gangrenosum, acne and HS)], severe HS and HS with additional inflammatory symptoms all belong to the category of autoinflammatory spectrum neutrophilic skin diseases. What is the translational message? The co‐occurence of inflammatory diseases with HS and the severity of HS, which we called 'complex HS', may indicate a more specific association with autoinflammation. The complex HS group represented a distinct population characterized by the early onset of HS. Pathogenic MEFV variants were increased not only in patients with PASH but also among patients fulfilling the criteria for 'complex HS'. The proinflammatory status caused by mutations in the MEFV gene may contribute to pathogenicity in complex HS. Linked Comment:  Contrassot and French. Br J Dermatol 2019; 180 :1294–1295 . Plain language summary available online Respond to this article